2016
DOI: 10.1002/pbc.26365
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and clinical integration of molecular profiling for target identification in pediatric solid tumors

Abstract: Pediatric molecular profiling is feasible, with more than a third of patients being eligible to receive targeted therapy, yet only a small proportion were treated with these therapies. Analysis at diagnosis may be useful for children with very poor prognosis tumsors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…Previous studies with smaller cohorts of patients have also documented frequent potential actionability, with over 90% of patients having at least one potentially actionable alteration [16, 45]. In contrast, other researchers found substantially lower percentages of alterations and potentially actionable alterations [5154], likely due to smaller panel sizes and interrogation of hot-spot regions, rather than the entire exon of the gene being interrogated. For instance, one large study with 2000 patients found that only 39% had at least one potentially actionable mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with smaller cohorts of patients have also documented frequent potential actionability, with over 90% of patients having at least one potentially actionable alteration [16, 45]. In contrast, other researchers found substantially lower percentages of alterations and potentially actionable alterations [5154], likely due to smaller panel sizes and interrogation of hot-spot regions, rather than the entire exon of the gene being interrogated. For instance, one large study with 2000 patients found that only 39% had at least one potentially actionable mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ALK and BRAF testing in selected tumours at relapse/progression is a standard of care in most pediatric oncology centres. However, consecutive single-marker testing is not compatible with clinical practice because of limited amount of tumour available (mostly diagnostic tru-cut), the intrinsic delays in each analysis and the overall cost [17]. The rapid development of high-throughput technologies and computational frameworks enables the examination of biological systems in unprecedented detail.…”
Section: Discussionmentioning
confidence: 99%
“…The need to explore the usefulness of drugs developed for adult patients arose among pediatric oncologists. The limited number of clinical trials available in children, as well as the lower biological knowledge of pediatric tumors led to the development of important precision medicine projects around the world [11][12][13][14][15][16][17]. In addition, the urgency to transfer biological information to patients in relapse/progression forced to start independent projects.…”
Section: Introductionmentioning
confidence: 99%
“…These initiatives have demonstrated the feasibility of such strategies at a single site or across multiple sites. 17 , 18 , 19 , 20 , 21 , 22 They have reported many genomic biomarkers or oncogenic drivers that have been proven useful to tailored patient management.…”
Section: Introductionmentioning
confidence: 99%